2021
DOI: 10.3390/metabo11060339
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Circulating Diagnostic Biomarkers for Coronary Microvascular Disease in Postmenopausal Women Using Machine-Learning Techniques

Abstract: Coronary microvascular disease (CMD) is a common form of heart disease in postmenopausal women. It is not due to plaque formation but dysfunction of microvessels that feed the heart muscle. The majority of the patients do not receive a proper diagnosis, are discharged prematurely and must go back to the hospital with persistent symptoms. Because of the lack of diagnostic biomarkers, in the current study, we focused on identifying novel circulating biomarkers of CMV that could potentially be used for developing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…Women tend to have more prevalent microvascular damage related to estrogen action in the endothelial cells. Botanical estrogens seem to have favorable actions with regard to vascular functions, with no risks to the reproductive tissue ( 137 ). Thus, botanical estrogens have the potential to improve cardiometabolic health during the menopause transition, but further work is needed in this area.…”
Section: Estrogen and Women's Healthmentioning
confidence: 99%
“…Women tend to have more prevalent microvascular damage related to estrogen action in the endothelial cells. Botanical estrogens seem to have favorable actions with regard to vascular functions, with no risks to the reproductive tissue ( 137 ). Thus, botanical estrogens have the potential to improve cardiometabolic health during the menopause transition, but further work is needed in this area.…”
Section: Estrogen and Women's Healthmentioning
confidence: 99%
“…Single studies have reported higher levels of serotonin, 75 stearic acid, 76 ornithine, 76 cardiac bridge integrator 1, 77 galactin‐3, 14 galectin‐4, 34 angiopoietin‐2 and tyrosine kinase‐2 receptor, 78 lymphocyte DNA damage, 79 NT‐proBNP (N‐terminal pro‐B‐type natriuretic peptide), 62 and red blood cell distribution width 62 in CMD compared with control subjects, and no difference in apolipoprotein‐C levels in CMD compared with controls. 31 In a study of 97 subjects with CMD, galectin‐4 levels correlated with myocardial blood flow reserve.…”
Section: Resultsmentioning
confidence: 99%